Caracterização molecular, taxonomia polifásica, susceptibilidade a antifúngicos e extratos das sementes de vatairea guianesnsis em isolados clínicos de Candida spp. na cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The C. albicans is the most frequently isolated fungus in humans healthy, being considered the main opportunistic pathogenic species, However, in recent decades, it has been observed a significant increase of other non-albicans species, involved both in colonization as in human infectious processes. The clinical manifestation but prevalent, This fungus, the woman is Vulvovaginal candidiasis (VVC). This study had the objective of making the molecular characterisation and polyphasic taxonomy of Candida species isolated from vaginal exsudate and describe their susceptibility profiles antifungals and extracts of Vatairea guianensis. The identification was performed by methods Classics (Microcultive, CHROMagar, Auxonograme), MALDI-TOF, multiplex PCR and molecular. In the analysis of genetic variability was made to AFLP.The colonization of Candida sp. in the vagina was statistically significant in patients aged 35 years or more, which made use of underwear fair and/or synthetic, in use of antibiotic therapy and who had CVV recurrent episodes. Of the 202 samples 37.1% (N = 75) was possible isolating yeasts Candida sp. C. albicans was the most isolated species (64%), followed by C. parapsilosis (20%), C. glabrata (5.3%), C. tropicallis (4%), C. haemolinus (4%) and C. krusei (1.3%) and C. lusitaniae (1.3%). Combinations of methods are required phenotypic and also carrying out additional evidence to the identification of Candida spp. molecular methods available confirm that the use phenotypic methods for clinical diagnosis must be cautious, have low accuracy in determination of Candida species not albicans and the identification of new species. The MALDI-TOF proved as an excellent tool for species identification of Candida sp, as it associates simple technique, procedures partially automated and mainly the speed of the result Microbiology, the limitation of this method is in the absence of a complete database. C. haemulonii, an emerging and rare species, was first identified in isolates of vaginal exudate asymptomatic women in Manaus. The vast majority of isolates of Candida sp., vaginal exudate, presented resistance to antifungals fluconazole, itraconazole, ketoconazole and Nystatin. The extracts of the seeds of V. guianensis presented only fungistatica activity in 04 isolates of Candida sp. vaginal exsudate. Thus, this research contributed to the epidemiological knowledge of species of Candida in vaginal flora of assintomaticas patients, and may guide the diagnosis in pathological conditions and being used in monitoring of emerging infections and drug resistant, because the variation of species according to geographical location should be taken into account between the epidemiological factors of CVV.
Keywords: Candida spp; Taxonomia Polofásica; MALDI-TOF; Candidíase vulvovagina; vataíre guianensis; CIENCIAS BIOLOGICAS